Penggunaan Minyak Biji Pala (Myristica fragrans, Houtt) Sebagai Bahan Anastesi Dalam Proses Pengangkutan Kualitas Spermatozoa Untuk Pemijahan Induk Ikan Nilem (Osteochillus hasselti, C.V.) - Sata Yoshida Srie Rahayu; Sanan Supriatna (EKOLOGIA, 2012)
Aquaculture of nilem fish needs parent and larvae. The good parent is available from research station with good facilities and management, so it can distribute to farmer by transportation. The important factors that should be notice in transportation process is usage of anaesthetic ingredients to exhilarate fish during transportation process. This research was used nutmeg bean oil contained of miristisin that able to exhilarate. The result of main research showed that the more nutmeg bean oil concentration the more fast nilem fish will be insensible, the lowest concentration (75 mg/l) sensible time of 97,11 minutes while the highest concentration (150 mg/l) showed insensible time of 10,13 minutes. The result of conscious time observation showed that 75 mg/l resulted conscious time of 17,5 second while 150 mg/l resulted concious time of 740 second. 150 mg/l concentration is the best concentration because it has the fastest insensible time of 10,13 minutes, the longest concious time of 740 second, has hatch value degree and the longest larvae-life and effective for exhilarate nilem fish. Nutmeg bean oil has influence towards sperm quality, but all of the treatments have the same effect (not significant) towards sperm quality, egg-impregnation degree, egg hatch and nilem fish larvae-life. Keywords: nutmeg bean oil, anaesthetic ingredients in delivery process, spermatozoa quality forspawning, nilem fish